Surface characterization of diblock copolymers containing poly(ethylene oxide) and various hydrophobic moieties - Logan, Jennifer; Marcano, Kyle; Palaskar, Dnyaneshwar; Wadgaonkar, Prakash; Jost, Robert W.; Wudl, Fred; Baker, Shenda M. (231st National Meeting of the American-Chemical-Society, 2006)

Abrupt shear thickening of aqueous solutions of hydrophobically modified poly(N,N `-dimethylacrylamide-co-acrylic acid) - Lele, Ashish K.; Shedge, Aarti; Badiger, Manohar V.; Wadgaonkar, Prakash; Chassenieux, Christophe (Macromolecules, 2010)
We report some new and interesting observations on the abrupt and large shear-induced thickening of aqueous solutions of hydrophobically modified poly(N,N'-dimethylacrylamide-co-acrylic acid). High molecular weight copolymer was prepared by free radical copolymerization of N,N'-dimethylacrylamide [DMA] and acrylic acid [AA] and was subsequently modified to different extents using a hydrophobic compound, namely, 3-pentadecylcyclohexylamine [3-PDCA], which is derived from a renewable resource material, cashew nutshell liquid [CNSL]. The structural elucidation of the base copolymer and the hydrophobically modified copolymers was performed by (1)H and (13)C NMR spectroscopy. The zero shear viscosities [eta(0)] of the hydrophobically modified polymers were lower than that of the precursor poly(N,N'-dimethylacrylamide-co-acrylic acid) until some critical polymer concentration, which increased with increase in hydrophobic modification. Above the critical concentrations, the eta(0) of the hydrophobically modified copolymers surpassed that of the precursor at the same concentration. At moderate shear rates some of these hydrophobically modified copolymers exhibited an abrupt shear-induced thickening in which the viscosity of the samples increased severalfold. We show here from creep experiments that thickening occurs only when the shear rate reaches a critical value, (gamma) over dot(crit), and that the thickened samples can be trapped in different metastable states by controlling the applied stress. Interestingly, the shear thickened samples showed further thickening upon decreasing the applied stress. Eventually, the metastable samples revert to their equilibrium states at characteristic time that depends on (small) probe stress.

High performance all-organic flexural piezo-FET and nanogenerator via nanoscale soft-interface strain modulation - Dhakras, Dipti; Gawli, Yogesh; Chhatre, Shraddha; Wadgaonkar, Prakash; Ogale, Satishchandra (Physical Chemistry Chemical Physics, 2014)
Flexural strain fields are encountered in a wide variety of situations and invite novel device designs for their effective use in sensing, actuating, as well as energy harvesting (nanogenerator) applications. In this work we demonstrate an interesting all-organic device design comprising an electrospun P(VDF-TrFE) fiber-mat built directly on a conducting PANI film, which is also grown on a flexible PET substrate, for flexural piezo-FET and nanogenerator applications. Orders of magnitude stronger modulation of electrical transport in PANI film is realized in this device as compared to the case of a similar device but with a uniform spin-coated P(VDF-TrFE) film. We find that in the flexural mode of operation, the interaction between the laterally modulated nanoscale strain field distributions created by the fibers and the applied coherent strain field strongly influences the carrier transport in PANI. The transport modulation is suggested to occur due to strain-induced conformational changes in P(VDF-TrFE) leading to changes in carrier localization-delocalization. We further show that the fiber-mat based device system also works as an efficient nanogenerator capable of delivering power for low power applications.

Clickable polyurethanes based on s- triazine ring containing aromatic diisocyanate bearing pendent alkyne group: synthesis and postmodification - Garg, Kavita; Chatterjee, Deepshikha; Wadgaonkar, Prakash (Journal of Polymer Science Part A Polymer Chemistry, 2017)
A new s-triazine ring containing aromatic diisocyanate bearing a pendent alkyne group, namely, 2,4-bis(4-isocyanatophenoxy)−6-(prop-2-yn-1-yloxy)−1,3,5-triazine was synthesized and reacted with various diols viz., 1,10-decanediol, tetraethylene glycol and polyethylene glycols in the presence of dibutyltin dilaurate as the catalyst to obtain a series of linear polyurethanes. The selected polyurethanes possessing pendent alkyne groups were postmodified with chemically diverse azides viz., 1-(azidomethyl)benzene, 1-(azidomethyl)pyrene, and methoxy end-caped poly(ethylene glycol) azide via copper-catalysed azide-alkyne Huisgen 1,3-dipolar cycloaddition. FTIR and 1H NMR spectra indicated quantitative click reaction. UV–vis and fluorescence spectroscopic analysis confirmed complete incorporation of pyrenyl groups indicating the formation of fluorescence active polyurethane by postmodification with 1-(azidomethyl)pyrene. TG analysis of polyurethanes indicated two stage weight loss and their thermal stability, as judged by T10 values, was governed by weight percent of urethane linkages. The water contact angle measurements revealed improved wettability with increased content of PEG either in the backbone of polyurethanes or as grafted chains. DLS and TEM studies confirmed that certain polyurethanes possessing PEG segments displayed self-assembly in aqueous solution, which was further supported by pyrene encapsulation studies using UV–vis spectroscopy. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2017, 55, 1008–1020
Keywords: Click chemistry; Diisocynate; Polyethelene Glycol; polyurethanes; Self- Assembly

Poly(ether urethane)s from aromatic diisocyanates based on lignin-derived phenolic acids - Kuhire, Sachin; Nagane, Samadhan S.; Wadgaonkar, Prakash (Polymer International, 2017)

Temperature and pH dual stimuli responsive PCL- b -PNIPAAm block copolymer assemblies and the cargo release studies - Patil, Sachin S.; Wadgaonkar, Prakash (Journal of Polymer Science Part A Polymer Chemistry, 2017)
A new atom transfer radical polymerization (ATRP) initiator, namely, 2-(1-(2-azidoethoxy)ethoxy)ethyl 2-bromo-2-methylpropanoate containing both “cleavable” acetal linkage and “clickable” azido group was synthesized. Well-defined azido-terminated poly(N-isopropylacrylamide)s (PNIPAAm-N3)s with molecular weights and dispersity in the range 11,000–19,000 g mol−1 and 1.20–1.28, respectively, were synthesized employing the initiator by ATRP. Acetal containing PCL-b-PNIPAAm block copolymer was obtained by alkyne–azide click reaction of azido-terminated PNIPAAm-N3 with propargyl-terminated PCL. Critical aggregation concentration (CAC) of PCL-b-PNIPAAm copolymer in aqueous solution was found to be 8.99 × 10−6 M. Lower critical solution temperature (LCST) of PCL-b-PNIPAAm copolymer was found to be 32 °C which was lower than that of the precursor PNIPAAm-N3 (36.4 °C). The effect of dual stimuli viz. temperature and pH on size and morphology of the assemblies of PCL-b-PNIPAAm block copolymer revealed that the copolymer below LCST assembled in spherical micelles which subsequently transformed to unstable vesicles above the LCST. Heating these assemblies above 40 °C led to the precipitation of PCL-b-PNIPAAm block copolymer. Whereas, at decreased pH, micelles of PCL-b-PNIPAAm copolymer disintegrate due to the cleavage of acetal linkage and precipitation of hydrophobic hydroxyl-terminated PCL. The encapsulated pyrene release kinetics from the micelles of synthesized PCL-b-PNIPAAm copolymer was found to be faster at higher temperature and at lower pH. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2017

Role of preparation parameters of Cu-Zn mixed oxide catalyst in solvent free glycerol carbonylation with urea - Charate, Shrinivas; Shinde, Suhas; Kondawar, Sharda; Desai, Uday; Wadgaonkar, Prakash; Rode, Chandrashekhar (Journal of the Indian Chemical Society, 2021)
Solvent-free carbonylation of glycerol with urea to glycerol carbonate (GC) was achieved over heterogeneous Cu-Zn mixed oxide catalyst. Cu-Zn catalysts with different ratios of Cu:Zn were prepared using co-precipitation (CP) and oxalate gel (OG) methods. As compared to CuO-ZnO(2:1) catalyst prepared by oxalate gel (OG) method, much higher conversion of glycerol and highest selectivity towards glycerol carbonate (GC) was achieved with CuO-ZnO_CP(2:1) catalyst. Physicochemical properties of prepared catalysts were investigated by using XRD, FT-IR, BET, TPD of CO2 and NH3 and TEM techniques. The effect of stoichiometric ratio of Cu/Zn, calcination temperature of CuO-ZnO catalysts and effect of reaction parameters such as molar ratio of substrates, time and temperature on glycerol conversion to GC were critically studied. Cu/Zn of 2:1 ratio, glycerol-urea 1:1 molar ratio, 145 degrees C reaction temperatures were found to be optimized reaction conditions to achieve highest glycerol conversion of 86% and complete selectivity towards GC. The continuous expel of NH 3 from reaction the mixture avoided formation of ammonia complex with CuO-ZnO catalyst. As a result of this, CuO-ZnO catalyst could be recycled up to three times without losing its initial activity.
Keywords: Co-precipitation (CP); Glycerol; Glycerol carbonate; Oxalate gel (OG)